Book Review: Focus: The Hidden Driver of Excellence. (March 2015) - Biswas, Supriya
Daniel Goleman, Focus: The Hidden Driver of Excellence . New Delhi: Bloomsbury Publishing India. 2014, 311 pp., ₹ 499. ISBN: 978 93 82951 79 7; 10987654321